2011
DOI: 10.1002/anie.201101841
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Silica Surface by Direct Silicon‐29 Dynamic Nuclear Polarization

Abstract: Buried truth: High‐field magic angle spinning dynamic nuclear polarization (MAS DNP) enhances the sensitivity of solid‐state NMR spectroscopy, but only for protonated surfaces. Direct 29Si DNP using the biradical TOTAPOL (see picture) circumvents this limitation by producing a 30‐fold enhancement of subsurface 29Si NMR signals in mesoporous silica, a material with applications in photonics, nanotechnology and catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
124
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 120 publications
(131 citation statements)
references
References 31 publications
7
124
0
Order By: Relevance
“…2) 29 Si spectra with less intensity due to a less efficient polarization with much lower enhancements compared to Q 4 enhancements ( Table 1). This difference between the direct-excitation and CP 29 Si DNP experiments has been reported previously for a mesoporous silica material, 21 which shows that the surface silicon sites (Q 2-3 ) are best polarized by CP, whereas, the sub-surface sites (Q 4 ) are polarized by directexcitation, which is also the case for the studied nanoparticles. As a result, it can be concluded that there is a preferential DNP polarization phenomenon in both silica based mesoporous and spherical materials, which leads to different DNP enhancements for different 29 Si sites, and as a result, different signal intensities in the spectra.…”
Section: Resultssupporting
confidence: 71%
See 4 more Smart Citations
“…2) 29 Si spectra with less intensity due to a less efficient polarization with much lower enhancements compared to Q 4 enhancements ( Table 1). This difference between the direct-excitation and CP 29 Si DNP experiments has been reported previously for a mesoporous silica material, 21 which shows that the surface silicon sites (Q 2-3 ) are best polarized by CP, whereas, the sub-surface sites (Q 4 ) are polarized by directexcitation, which is also the case for the studied nanoparticles. As a result, it can be concluded that there is a preferential DNP polarization phenomenon in both silica based mesoporous and spherical materials, which leads to different DNP enhancements for different 29 Si sites, and as a result, different signal intensities in the spectra.…”
Section: Resultssupporting
confidence: 71%
“…56 These values are similar to the ones reported previously. 19 However, B30% larger enhancements were observed for direct-excitation 29 Si DNP experiments recently by using a different microwave (mW) irradiation frequency, under the so-called 21 The power of the DNP enhancements leads to the observation of spectra with high sensitivity in a very short experiment time (B60 or B40 seconds for the 1D CP or direct-excitation experiments, respectively, for experimental parameters see the caption of Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations